2010
DOI: 10.2174/1745017901006010079
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Spanish Patients with Liver Transplant

Abstract: Background:Liver transplantation is the optimal method of treatment in patients with end-stage liver failure. Transplantation medicine has significantly progressed in the last time, but some psychology and psychosomatic problems still remain unsolved. Health-Related Quality of Life (HRQL) in liver transplant is considered a useful measure of evolutionary process of the illness. Objective:The authors analyzed the evolution of HRQL in pre-transplant (waiting-list patients) and post-transplant (first year after l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…There are several studies focusing on social and health aspects of older adults in Spain that include QoL scales (Azpiazu Garrido et al ., 2003; Perez-San-Gregorio et al ., 2010). Longitudinal studies on aging have also been carried out (Zunzunegui et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies focusing on social and health aspects of older adults in Spain that include QoL scales (Azpiazu Garrido et al ., 2003; Perez-San-Gregorio et al ., 2010). Longitudinal studies on aging have also been carried out (Zunzunegui et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on quality of life in patients following liver transplantation [2][3][4][5][6][7][8][9][10][11]. Most of them used the SF-36 [2,3,[5][6][7][8][9]. Advantages of this survey are the opportunity of looking across a broad range of conditions and to compare scores with published norms of healthy or diseased population.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on quality of life in liver transplant recipients [2][3][4][5][6][7][8][9][10][11]. These studies used typically standardized measures for the evaluation of quality of life such as the SF-36.…”
Section: Introductionmentioning
confidence: 99%
“…Patients often describe LT as a “re-birth”, meaning the biological and psychological aspect related to a new donated life. Along with the obvious psychological benefit of passing from facing death to a longer life expectancy, the health and liver-related symptoms gain after LT reflects in a well-documented improvement in health [ 45 48 ]. Physicians often describe LT as a “reverse time” story, somehow putting back the biological clock to the time before ESLD.…”
Section: Discussionmentioning
confidence: 99%